Key agreement protocol in Braid group representation level - Tvarijonas, Povilas; Sakalauskas, Eligijus; Dosinas, Gediminas Simonas (Lietuvos matematikos rinkinys, 2021)
In this paper the key agreement protocol is given and the applicationof it in Braid groups is suggested. The one way of protocol is being justified.
Keywords: key agreement protocol; Braid groups